Mutational analysis of disease relapse in patients allografted for acute myeloid leukemia - Quek, L; Ferguson, P; Metzner, M; Ahmed, I; Kennedy, A; Garnett, C; Jeffries, S; Walter, C; Piechocki, K; Timbs, A; Danby, R; Raghavan, M; et al. (American Society of Hematology, 2016)
Disease relapse is the major cause of treatment failure after allogeneic stem cell transplantation (allo-SCT) in acute myeloid leukemia (AML). To identify AML-associated genes prognostic of AML relapse post–allo-SCT, we resequenced 35 genes in 113 adults at diagnosis, 49 of whom relapsed. Two hundred sixty-two mutations were detected in 102/113 (90%) patients. An increased risk of relapse was observed in patients with mutations in WT1 (P = .018), DNMT3A (P = .045), FLT3 ITD (P = .071), and TP53 (P = .06), whereas mutations in IDH1 were associated with a reduced risk of disease relapse (P = .018). In 29 patients, we additionally compared mutational profiles in bone marrow at diagnosis and relapse to study changes in clonal structure at relapse. In 13/29 patients, mutational profiles altered at relapse. In 9 patients, mutations present at relapse were not detected at diagnosis. In 15 patients, additional available pre–allo-SCT samples demonstrated that mutations identified posttransplant but not at diagnosis were detectable immediately prior to transplant in 2 of 15 patients. Taken together, these observations, if confirmed in larger studies, have the potential to inform the design of novel strategies to reduce posttransplant relapse highlighting the potential importance of post–allo-SCT interventions with a broad antitumor specificity in contrast to targeted therapies based on mutational profile at diagnosis.